Comparative analysis of the replication of bovine herpesvirus 1 (BHV1) and BHV5 in bovine derived-neuron-like cells - Cardoso, Tereza Cristina [UNESP]; Ferreira, Helena Lage; Okamura, Lucas Hidenori [UNESP]; Oliveira, Bruna R. S. M. [UNESP]; Rosa, Ana Carolina Guedes [UNESP]; Gameiro, Roberto [UNESP]; Flores, Eduardo Furtado (Springer Nature, 2015)
Members of the subfamily Alphaherpesvirinae use the epithelium of the upper respiratory and/or genital tract as preferential sites for primary replication. However, bovine herpesvirus 5 (BoHV5) is neurotropic and neuroinvasive and responsible for meningoencephalitis in cattle and in animal models. A related virus, BoHV1 has also been occasionally implicated in natural cases of neurological infection and disease in cattle. The aim of the present study was to assess the in vitro effects of BoHV1 and BoHV5 replication in neuron-like cells. Overall, cytopathic effects, consisting of floating rounded cells, giant cells and monolayer lysis, induced by both viruses at 48 h postinfection (p.i.) resulted in a loss of cell viability and high virus titres (r = 0.978). The BoHV1 Cooper strain produced the lowest titres in neuron-like cells, although viral DNA was detected in infected cells during all experiments. Virus replication in infected cells was demonstrated by immunocytochemistry, flow cytometry and qPCR assays. BoHV antigens were better visualized at 48 h p.i. and flow cytometry analysis showed that SV56/90 and Los Angeles antigens were present at higher levels. In spite of the fact that BoHV titres dropped at 48 h p.i, viral DNA remained detectable until 120 h p.i. Sensitive TUNEL (terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling) and annexin V assays were used to identify apoptosis. BoHV5 induced death in approximately 50 % of cells within 24 h p.i., similar to what has been observed for BoHV1 Los Angeles. Infection with the BoHV1 Cooper strain resulted in 26.37 % of cells being in the early stages of apoptosis; 63.69 % of infected cells were considered viable. Modulation of mitochondrial function, as measured by mitochondrial membrane depolarization, was synchronous with the virus replication cycle, cell viability and virus titres at 48 h p.i. Our results indicate that apoptosis plays an important role in preventing neuronal death and provides a bovine-derived in vitro system to study herpesvirus-neuron interactions.
Keywords: Virology; Medical microbiology; Infectious diseases